Eliminasi Sweet Potato Feathery Mottle Virus (SPFMV) pada Empat Kultivar Ubijalar Unggul Lokal Asal Papua melalui Teknik Kultur Meristem - , Barahima; Wasgito Purnomo (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2003)
The objective of this research was to eliminate Sweet Potato Feathery Mottle Virus (SPFMV) infection from local superior sweet potato varieties (PN-II, Maria, Seri, and Numfor) by using meristem culture technique. Shoot tips of sweet potato were grown on solid MS modified medium enriched with naphthalene acetic acid (NAA) and benzyl adenine (BA) with various concentrations. Growth and development of explants were recorded for three months. The results showed that elimination of SPFMV infection of four varieties by using shoot tip explants were successfully achieved. Shoot tips were the best explants used to eliminate SPFMV infection. Murashige and Skoog (MS) modification called Ub I medium, which enriched with NAA (0.02 mg/l) and BA (0.2 mg/l) is the best medium for developing meristem segment of sweet potato. Nitrocellulose membrane-enzyme linked immunosorbent assay (NCM- ELISA) analysis showed that plantlets produced from shoot tip explants of four varieties, tested were free from SPFMV infection. The plantlets of four varieties were maintained in in vitro culture in Biotechnology Laboratory, Faculty of Agriculture, State University of Papua (UNIPA), Manokwari. Key words: Sweet potato, SPFMV; Meristem culture technique